Growth differentiation factor 15 and cardiovascular risk: individual patient meta-analysis - Kato, Eri Toda; Morrow, David A; Guo, Jianping; Berg, David D; Blazing, Michael A; Bohula, Erin A; Bonaca, Marc P; Cannon, Christopher P; de Lemos, James A; Giugliano, Robert P; Jarolim, Petr; Kempf, Tibor; et al. (European heart journal, 2023)
Levels of growth differentiation factor 15 (GDF-15), a cytokine secreted in response to cellular stress and inflammation, have been associated with multiple types of cardiovascular (CV) events. However, its comparative prognostic performance across different presentations of atherosclerotic cardiovascular disease (ASCVD) remains unknown. An individual patient meta-analysis was performed using data pooled from eight trials including 53 486 patients. Baseline GDF-15 concentration was analyzed as a continuous variable and using established cutpoints (<1200 ng/L, 1200-1800 ng/L, > 1800 ng/L) to evaluate its prognostic performance for CV death/hospitalization for heart failure (HHF), major adverse cardiovascular events (MACE), and their components using Cox models adjusted for clinical variables and established CV biomarkers. Analyses were further stratified on ASCVD status: acute coronary syndrome (ACS), stabilized after recent ACS, and stable ASCVD. Overall, higher GDF-15 concentration was significantly and independently associated with an increased rate of CV death/HHF and MACE (P < 0.001 for each). However, while GDF-15 showed a robust and consistent independent association with CV death and HHF across all presentations of ASCVD, its prognostic association with future myocardial infarction (MI) and stroke only remained significant in patients stabilized after recent ACS or with stable ASCVD [hazard ratio (HR): 1.24, 95% confidence interval (CI): 1.17-1.31 and HR: 1.16, 95% CI: 1.05-1.28 for MI and stroke, respectively] and not in ACS (HR: 0.98, 95% CI: 0.90-1.06 and HR: 0.87, 95% CI: 0.39-1.92, respectively). Growth differentiation factor 15 consistently adds prognostic information for CV death and HHF across the spectrum of ASCVD. GDF-15 also adds prognostic information for MI and stroke beyond clinical risk factors and cardiac biomarkers but not in the setting of ACS.